Pemetaan Resiko dan Kerentanan Perubahan Iklim di Kabupaten Jember Provinsi Jawa Timur: Penelitian - Irfani Zahira Rustiawan; Muhammad Zaky Ibnu Malik (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Climate change is a strategic issue that requires serious attention because it affects various sectors, including agriculture. Jember Regency is one of the regions that plays an important role in meeting national rice needs and was the largest rice producer in East Java in 2015, producing around 10,048,980 quintals. Climate change can affect agricultural productivity, such as changes in temperature and rainfall that impact the extent of rice fields and the quality of agricultural products. Therefore, there is a risk of adverse effects from climate change. To mitigate these impacts, adaptive actions are needed, including conducting vulnerability and climate risk assessments. The method used is descriptive with a spatial approach. The data used are secondary data, while the analysis techniques include exposure classes and sensitivity classes. The research results show that as exposure classes and sensitivity classes increase, the level of vulnerability and risk to climate change also increases, and vice versa. This study is expected to serve as a reference for decision-making regarding agricultural risk management policies in Jember Regency